Analisis Selektivitas Alat Tangkap Gillnet pada Penangkapan Ikan Bilih (Mystacoleucus padangensis Blkr) di Danau Singkarak, Sumatera Barat - Bukhari Bukhari; Mas Eriza; Yuspardianto Yuspardianto; Suparno Suparno (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
The threat of extinction for bilih fish is caused by uncontrolled fishing with various types of non-selective fishing gear. dependence of fishing communities on bilih fish and there is no community-based bilih fish conservation area. This study aims to examine the various types of gillnet mesh sizes used in catching Bilih fish at Singkarak Lake, west Sumatera. Research data collection used three mesh sizes, namely gillnet mesh size 5/8 inch, 3/4 inch, and 1 inch in four villages, namely Nagari Guguak Malalo and Nagari Batu Taba (South Batipuah District, Tanah Datar Regency) and Nagari Muaro Paninggahan and Muaro Pingai (Junjung Sirih District, Solok Regency). The results showed that Bilih fish caught with gillnet mesh size of 5/8 inches had an average length of 6.680 cm and an average weight of 2.652 grams, and Bilih fish caught with gillnet mesh size 3/4 inches with an average length of 7.594 cm. and an average weight of 4.112 g, while the number of fish caught with gillnet mesh size 1 inch with an average length of 9.460 cm and an average weight of 8.200 g.